Discourse Markers as Functional Elements - Matei, Mădălina (Transilvania University Press, 2010)
The aim of this paper is to justify the necessity of adopting a functional approach to the study of discourse markers but also to revisit the theories connected to functionalism in linguistics and to define what a functional approach to discourse markers would actually imply. In the first part of the paper, the focus will be placed on functionalism and on those theories which are most relevant for a functional analysis of discourse markers. The second part of the paper will be centered on discourse markers, their discursive and pragmatic functions as well as on their connection to functional linguistics.
Keywords: pragmatic meaning; grounding; functionalism; discursive goal.